NEPHROPROTECTIVE OF ANTHOCYANIN PIGMENTS EXTRACT FROM RED CABBAGE (BRASSICA OLERACEA L. VAR. CAPITATA F. RUBRA) AGAINST GENTAMICIN-CAPTOPRIL-INDUCED NEPHROTOXICITY IN RATS - Shiyan, Shaum; Herlina, Herlina; Rizkika Sari, Lita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Red cabbage (Brassica oleracea L. var. Capitata f. rubra) has a fairly high anthocyanin content and is a source of powerful antioxidants. This study is basic for the development of a nutraceutical, which has nephroprotective activity. Methods: Red cabbage was extracted using ethanol and water with a mixture of citric acid with a variation of 1, 2, and 3%. The total anthocyanin was determined with pH-differential method. The Wistar strain male rats were divided into five groups. Group 1 as a negative control, Group 2 as a positive control treated with Vitamin E dose of 400 mg/kg BW day. Groups 3–5 were treated with three different extract dose of 100, 200, and 400 mg/kg BW. Gentamicin was given intraperitoneally and captopril orally for 3 days. Extracts and Vitamin E were administrated orally for 15 days after induction of gentamicin-captopril. Nephroprotective activity was determined by measuring the levels of serum creatinine, blood ureum, and macroscopic kidney. Results: The combination of 96% ethanol and citric acid 3% showed the percent of free radical 2,2-diphenyl-1-picrylhydrazyl arrest of 75.23% and contained 53.49 ± 5.01 mg/L of total anthocyanin. The anthocyanin pigment from red cabbage extract can decrease the levels of creatinine and ureum, which dose of 100 mg/kg BW showed the highest value of 48.72%. There were differences in the macroscopic morphology in the rat kidney. Conclusion: Based on the results, we concluded that ethanol with 3% citric acid produced higher anthocyanin and showed nephroprotective activity.